2012
DOI: 10.1152/ajpregu.00057.2012
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 in the subfornical organ inhibits the dipsogenic response to angiotensin II

Abstract: in the subfornical organ inhibits the dipsogenic response to angiotensin II. Am J Physiol Regul Integr Comp Physiol 303: R921-R928, 2012. First published August 29, 2012 doi:10.1152 doi:10. /ajpregu.00057.2012 for the calcium-regulating glycoprotein hormone stanniocalcin-1 (STC-1) have been found within subfornical organ (SFO), a central structure involved in the regulation of electrolyte and body fluid homeostasis. However, whether SFO neurons produce STC-1 and how STC-1 may function in fluid homeostasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…44 Recent animal studies demonstrated that the calcium-regulating glycoprotein stanninocalcin-1, which functions within the SFO, may modulate angiotensin II to regulate fluid intake. 45 Also, a pediatric study that examined the effect of ionized hypocalcemia on organ dysfunction early in the ICU stay found that treatment with furosemide was associated with hypocalcemia, 46 perhaps contributing a partial explanation for our ionized calcium findings. Nonetheless, the small difference inionized calcium seen in this study is not a clinically meaningful difference; how this difference contributes to thirst in ICU patients will require further study.…”
Section: Discussionmentioning
confidence: 85%
“…44 Recent animal studies demonstrated that the calcium-regulating glycoprotein stanninocalcin-1, which functions within the SFO, may modulate angiotensin II to regulate fluid intake. 45 Also, a pediatric study that examined the effect of ionized hypocalcemia on organ dysfunction early in the ICU stay found that treatment with furosemide was associated with hypocalcemia, 46 perhaps contributing a partial explanation for our ionized calcium findings. Nonetheless, the small difference inionized calcium seen in this study is not a clinically meaningful difference; how this difference contributes to thirst in ICU patients will require further study.…”
Section: Discussionmentioning
confidence: 85%
“…SFO microinjection was performed as previously described (Moreau et al, 2012; Wei et al, 2015). Briefly, rats were anesthetized (ketamine 100 mg/kg + xylazine 10 mg/kg IP) and positioned in a stereotaxic apparatus (Kopf Instruments; Tujunga, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Human and rat STC1 share 99% identity and the recombinant hSTC1 has been previously used in studies in rat Moreau et al, 2012;Ookata et al, 2001). Recombinant fish STC1-A and STC1-B isoforms (from puffer fish, Tetraodon nigroviridis) were produced and kindly provided by Dr. Mirjam Czjzek (Groisillier et al, 2010).…”
Section: Hormonesmentioning
confidence: 99%